1997
DOI: 10.1136/vr.140.10.247
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of nursery depopulation on the persistence of porcine reproductive and respiratory syndrome virus and the productivity of 34 farms

Abstract: Nursery depopulation has been described as an effective strategy for improving the performance of weaned pigs. In order to assess whether the strategy was effective under a wide range of conditions, a study was carried out on 34 farms in the USA. Four groups with different depopulation protocols were designed on the basis of the location of the depopulated facility (on site vs off site) and the period for which the nursery remained empty (seven days vs 14 days). The changes in average daily liveweight gain, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…PRRSV continues to be an economically significant health problem for swine producers worldwide with an estimated reported loss of $228 per inventoried sow (8,9). Immunity to PRRSV has eluded researchers and remains a complicated and poorly understood process.…”
Section: Introductionmentioning
confidence: 99%
“…PRRSV continues to be an economically significant health problem for swine producers worldwide with an estimated reported loss of $228 per inventoried sow (8,9). Immunity to PRRSV has eluded researchers and remains a complicated and poorly understood process.…”
Section: Introductionmentioning
confidence: 99%
“…The eradication of PRRS appears to be a difficult issue, at least to date. Some studies have shown that by using management strategies, such as segregated early weaning and other modifications of the 'all-in, all-out' system, the syndrome can be eliminated (Dee et al, 1993(Dee et al, , 1997. However, such strategies are not always successful and cannot be easily applied, depending on the facilities and hardware of each enterprise (Dee et al, 1993(Dee et al, , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Field evidence strongly suggests that PRRSV infection makes pigs more susceptible to bacterial diseases in nursery and grow-finish pigs (2). Combined porcine reproductive and respiratory syndrome virus (PRRSV) and Streptococcus suis infections are common (10,14,16) and can be especially problematic to control with conventional medication and vaccination regimens (1,15).…”
mentioning
confidence: 99%